Analysis Of The Overturning Of Heavy Vehicles In The “The Adioses” Curve Of The Highway Pamplona-Cúcuta (2021)
Over time, it has been observed that accidents due to vehicle overturning in the “The Adioses” curve of the Pamplona - Cúcuta road are a fairly frequent problem due to several factors such as: high speeds, absence of traffic signs, driver maneuvers, among others. This is why this section of the road has been classified as a critical accident point. The vehicles that are most affected are heavy vehicles (truck tractors), which due to their large size have a high gravity center, which hinders their stability compared to other vehicles. Another important aspect that it is taken into account is the characteristics of the road that can modify the load distribution in the vehicle. All these aspects are evaluated through a case study which allows calculating the stability factor for a particular heavy vehicle and calculating the safe traffic speed for this vehicle in the specified sector.